USING GEOGRAPHIC INFORMATION SYSTEMS TO INCREASE PRODUCTIVITY AND REDUCE WORKPLACE DIFFICULTIES (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Based on the findings of this study, researchers who are working in the field of information systems will be supplied with a research framework as well as an overview of geographic information systems. This page contains a research framework for geographic information systems (GIS), as well as an overview of the fundamental capabilities, features, and functions of GIS. Additionally, this article describes the research framework. It is also recommended that research potential be investigated in a wide range of different domains, including the management of geographic information systems (GIS), the implications of organisational structures, the challenges of working together, evaluations of the efficiency of decision-making, and the social effects in both industrialised and developing nations. Since its inception in the 1960s, multicriteria analysis has been successfully used in a wide variety of fields of study. It is a family of operations research and management science methodologies that has successfully been utilised. Creating a method that can be utilised to combine multicriteria analysis with geographical information systems is the major purpose of this study that is being done. The reality of the matter is that geographic information systems are susceptible to a range of restrictions when it comes to the provision of help for the process of making decisions regarding spatial matters. In order to discover a solution to these limitations, it is recommended that the methodologies of operations research and management science, in particular those associated with MCA, be combined with the tools of geographic information systems technology. This type of integration is intended to ultimately result in the establishment of a system that is referred to as the "spatial decision support system." The purpose of this system is to offer aid to decision-makers who are dealing with difficulties that are related to space. As a result of this, a design for an SDSS is also offered as a consequence.